Blended learning curriculum approach: a systematic review of the challenges for students - Razali, Fazilah; Sulaiman, Tajulariffin; Mohd Ayub, Ahmad Fauzi; Abdul Majid, Noraziela (Abdullah Kuzu, 2021)
This study generated a Systematic Literature Review (SLR) by following proven and stringent guidelines. PRISMA 2009 is used to retrieve 15 study papers that were selected and analysed in the SLR. The scientific research on the complexities of blended learning program approaches to students has been examined. The papers' publishing years range from 2015 to 2020. The methodological designs, foci, and results of the experiments have all been thoroughly examined. According to the study, the major problems and challenges that students faced in learning included getting distracted in the classroom due to large class size, inaccessibility to online lessons due to Learning Management System (LMS) severe crash, complexity of internet communication with teachers and classmates, lack of skills and experience with digital tools, and time management for learning.